Pengaruh Pembelajaran IPS Terhadap Perwujudan Sikap Anak Sekolah Dasar Kelas Rendah - Salsa, Linda; Tarigan, Emia Rita Pitriani; Sumarni, Rindi; Rustini, Tin (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research focused on discussing how social studies learning affects the development of traits in low-grade children in elementary school. In this research, the method used is qualitative by relying on various existing literature. The researcher wanted to find out whether social studies learning has a significant influence on the realization of children's traits, such as honesty, awareness, and loyalty. Existing data in this study were obtained through the results of literacy studies using analytical techniques. The results showed that social studies learning has a positive and significant influence on children's embodiment. Social studies learning is a process of exploring various things about the science of society whose study is narrowed with certain boundaries in everyday life. The characteristics of social studies learning focus on the process that occurs in it, rather than focusing on the results. Children who receive social studies learning have better traits than children who do not receive social studies learning. This result shows that social studies learning is an effective in improving children's character. Not only provides knowledge and skills in intellectual or practical matters, social studies also instill valuable and meaningful moral attitudes. Thus, this study recommends that social studies learning should be an integral part of the primary school curriculum to improve children's character and help them become new socially minded individuals.